2016
DOI: 10.1016/j.numecd.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

The consumption of fish cooked by different methods was related to the risk of hyperuricemia in Japanese adults: A 3-year follow-up study

Abstract: This 3-year follow-up study showed that the consumption of raw or roasted fish, but not boiled or fried fish, was related with a higher risk of hyperuricemia in Japanese adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Ren et al. showed that roasted and raw fish consumption contributed to hyperuricemia [ 11 ]. Evidence have shown factors such as sex, alcohol consumption, and age are risk factors of CKD and hyperuricemia [ 1 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ren et al. showed that roasted and raw fish consumption contributed to hyperuricemia [ 11 ]. Evidence have shown factors such as sex, alcohol consumption, and age are risk factors of CKD and hyperuricemia [ 1 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ren et al. performed a 3-year follow-up study and confirmed that the consumption of raw or roasted fish, but not boiled or fried fish, was related to a high risk of hyperuricemia in Japanese adults [ 11 ]. The leading causes of CKD 3–4 include diabetes and hypertension [ 9 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that the serum uric acid level increased with increasing consumption of seafood and their products. 5,6 But according to a recent review, few studies had investigated the associations between fish consumption and metabolic syndrome prevalence. 7 Fish consumption may also have been negatively associated with waist circumference (WC), 8 serum lipids, 9 and blood pressure level.…”
Section: Introductionmentioning
confidence: 99%